Aluminum trifate‑cocatalyzed radical copolymerization of styrene and ethyl acrylate - Guyo, Upenyu; Otto, Daniel P.; Young, Desmond A.; Vosloo, Hermanus C. M. (Springer, 2021)
Various random copolymers, poly(styrene-co-ethyl acrylate), were synthesized by free radical bulk copolymerization cocatalyzed by aluminum trifate (Al(OTf)3). The experimental conditions for the polymerization reactions, which include the amount of cocatalyst, polymerization time and ratio of styrene to ethyl acrylate, were investigated. The copolymer molecular weights were determined by gel permeation chromatography coupled to multi-angle laser light scattering. Compositional analysis was performed using proton nuclear magnetic resonance spectrometry. Electron paramagnetic resonance spectroscopy was also used to study the radical species which form in the presence or absence of Al(OTf)3. Kinetic studies were performed by determining monomer conversions as a function of time on gas chromatography. It was found that Al(OTf)3 accelerated the rate of polymerization signifcantly while also increasing the polymer molecular weights for a given conversion compared to the reactions where the trifate was absent. Al(OTf)3 can be a signifcantly more cost-efective and abundant alternative polymerization cocatalyst compared to some of the rare lanthanide trifates.